Exercise combined with artificial gravity and exercise only countermeasures prevent organ and blood vessel morpholgical changes induced by 55 days HDT bedrest - Arbeille, P.; Zuj, K.; Guillon, L. (Frontiers in Physiology, 2024)
BackgroundChanges in blood vessel properties have been identified with confinement, spaceflight, bedrest, and dry immersion. Subsequently, it was suspected that other organs may also be affected in these extreme environments. The purposes of the current study were to determine the effects of head-down bedrest (HDT) on cardiovascular and organ measurements made using ultrasound imaging similar to that currently available on the International Space Station, and to evaluate the efficacy of two different countermeasure protocols in preventing any observed changes in the ultrasound measurements with HDT.MethodsUltrasound measures were conducted on 24 individuals (3 groups of 8) pre HDT and on day 55 of the HDT. The control group (C°) remained in passive HDT for the 55 days, the C1 group performed aerobic exercise daily (EX), and the C2 group practiced aerobic exercise under artificial gravity conditions (EX-AG). Fifteen parameters were measured on 10 different organs and blood vessels including the right common carotid artery, abdominal aorta, right tibial artery, left ventricle, right jugular vein, portal vein, right kidney, cervical and lumbar vertebra, and the vastus intermedius muscle.ResultsHDT resulted in changes for many of the parameters investigated. Observed changes in carotid IMT and distensibility, cardiac ejection fraction, portal vein diameter, and vastus intermedius muscle thickness were attenuated with EX and EX-AG, with EX-AG having a greater effect than exercise alone on measures of carotid distensibility.ConclusionResults from this study indicate changes in many structures assessed with ultrasound imaging after 55 days of HDT bedrest with some changes being attenuated with the two investigated countermeasure protocols.